Differences in Distribution and Detection Rate of the [68Ga]Ga-PSMA Ligands PSMA-617, -I&T and -11-Inter-Individual Comparison in Patients with Biochemical Relapse of Prostate Cancer - Falk Gühne; Stefanie Radke; Thomas Winkens; Christian Kühnel; Julia Greiser; Philipp Seifert; Robert Drescher; Martin Freesmeyer (MDPI AG, 2021)
The biochemical relapse of prostate cancer is diagnostically challenging but of high clinical impact for subsequent patient treatment. PET/CT with radiolabeled PSMA ligands outperforms conventional diagnostic methods in the detection of tumor recurrence. Several radiopharmaceuticals were and are available for use. The aim of this study was to investigate whether the routinely applied [68Ga]Ga-PSMA ligands PSMA-617, -I&T and -11 (HBED-CC) differ in physiological and pathological distribution, or in tumor detection rate. A retrospective evaluation of 190 patients (39 patients received PSMA-617, 68 patients PSMA-I&T and 83 patients PSMA-11) showed significant differences in tracer accumulation within all organs examined. The low retention within the compartments blood pool, bone and muscle tissue is a theoretical advantage of PSMA-11. Evaluation of tumor lesion uptake and detection rate did not reveal superiority of one of the three radiopharmaceuticals, neither in the whole population, nor in particularly challenging subgroups like patients with very low PSA levels. We conclude that all three [68Ga]Ga-PSMA ligands are equally feasible in this clinically important scenario, and may replace each other in case of unavailability or production restrictions.